Non-lamellar lyotropic liquid crystalline nanoparticles as nanocarriers for enhanced drug encapsulation of atorvastatin calcium and proanthocyanidins - Maslizan, Mardhiah; Haris, Muhammad Salahuddin; Ajat, Mokrish; Md Jamil, Siti Nurul Ain; Azhar, Shah Christirani; Zahid, N. Idayu; Mat Azmi, Intan Diana (Elsevier BV, 2024)
Atorvastatin calcium (ATV) and proanthocyanidins (PAC) have a strong antioxidant activity, that can benefit to reduce the atherosclerotic plaque progression. Unfortunately, the bioavailability of ATV is greatly reduced due to its limited drug solubility while the PAC drug is unstable upon exposure to the atmospheric oxygen. Herein, the lyotropic liquid crystalline nanoparticles (LLCNPs) constructed by a binary mixture of soy phosphatidylcholine (SPC) and citric acid ester of monoglyceride (citrem) at different weight ratios were used to encapsulate the hydrophobic ATV and hydrophilic PAC. The LLCNPs were further characterized by small-angle X-ray scattering and dynamic light scattering. Depending on the lipid composition, the systems have a size range of 140–190 nm and were able to encapsulate both drugs in the range of 90–100. Upon increasing the citrem content of drug-loaded LLCNPs, the hexosomes (H2) was completely transformed to an emulsified inverse micellar (L2). The optimum encapsulation efficiency (EE) of ATV and PAC were obtained in citrem/SPC weight ratio 4:1 (L2) and 1:1 (H2), respectively. There was a substantial change in the mean size and PDI of the nanoparticles upon 30 days of storage with the ATV-loaded LLCNPs exhibiting greater colloidal instability than PAC-loaded LLCNPs. The biphasic released pattern (burst released at the initial stage followed by the sustained released at the later stage) was perceived in ATV formulation, while the burst drug released pattern was observed in PAC formulations that could be attributed by its internal H2 structure. Interestingly, the cytokine studies showed that the PAC-LLCNPs promisingly up regulate the expressions of tumor necrosis factor-alpha (TNF-α) better than the drug-free and ATV-loaded LLCNPs samples. The structural tunability of citrem/SPC nanoparticles and their effect on physicochemical characteristic, biological activities and potential as an alternative drug delivery platform in the treatment of atherosclerosis are discussed.